HEALTHY LIFE AWARENESS IMPROVEMENT THROUGH HANDWASH HEALTH PROMOTION IN THE KINDERGARTEN OF SENTUL VILLAGE, TANGGULANGIN SUB-DISTRICT, SIDOARJO DISTRICT - Agus Sulistyowati; Nur Azizah; Belinda Anggraini Putri; Eno Desty Masrikat; Lailis Rizky Amalia; Mirza Safira; Yani Oksanti Putri; Indra Muhammad (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2019)
An increase in awareness of healthy living through health promotion in the Kindergarten of Sentul Village, Tanggulangin Sub-District, Sidoarjo District is a form of education in the form of counseling aimed at fostering and enhancing healthy behavior early, especially in recognizing good and proper hand washing procedures. The activity was held on November 27, 2018 at the Kindergarten of Sentul Village, Tanggulangin Sub-District, Sidoarjo District. The target is the students of the Kindergarten of Sentul Village, Tanggulangin Sub-District, Sidoarjo District. Before the implementation of these activities, there is a process of preparing activities for 3 weeks before the activities are carried out, starting from the selection of health counseling materials to the submission of permits to related parties. As an evaluation, the activity was attended by 41 students and 4 teachers, participants participated in the activity with enthusiasm and conduciveness, the activities could be carried out on time smoothly. Keywords: Handwash health promotion, kindergarten, healthy life awareness.